2022
DOI: 10.18632/aging.203877
|View full text |Cite
|
Sign up to set email alerts
|

Hyperintensities of middle frontal gyrus in patients with diabetic optic neuropathy: a dynamic amplitude of low-frequency fluctuation study

Abstract: Diabetic optic neuropathy (DON) is a diverse complication of diabetes and its pathogenesis has not been fully elucidated. The purpose of this study was to explore dynamic cerebral activity changes in DON patients using dynamic amplitude of low-frequency fluctuation (dALFF). In total, 22 DON patients and 22 healthy controls were enrolled. The dALFF approach was used in all participants to investigate dynamic intrinsic brain activity differences between the two groups. Compared with HCs, DON patients exhibited s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 79 publications
0
1
1
Order By: Relevance
“… 41 Our findings are in accordance with all the above ophthalmology-related diseases. However, our results are partially disparate from several articles on the same topic, 24 , 42 mainly because the sample sizes in theses three articles were both relatively small, and the technologies used were different, which may cause the difference. The medial frontal gyrus and orbital gyri both belong to the prefrontal cortex, which covers the anterior part of the frontal lobe and participates in various critical cognitive and emotional processing tasks.…”
Section: Discussioncontrasting
confidence: 89%
“… 41 Our findings are in accordance with all the above ophthalmology-related diseases. However, our results are partially disparate from several articles on the same topic, 24 , 42 mainly because the sample sizes in theses three articles were both relatively small, and the technologies used were different, which may cause the difference. The medial frontal gyrus and orbital gyri both belong to the prefrontal cortex, which covers the anterior part of the frontal lobe and participates in various critical cognitive and emotional processing tasks.…”
Section: Discussioncontrasting
confidence: 89%
“…Retinopathy is a common diabetes complication, which can lead to visual impairment. Most studies on T2DM patients with optic nerve-related complications have reported negative alterations in the MOG and the precuneus, including decreased synchronous neural activities, decreased dynamic cerebral activity ( Yang et al, 2022 ), lower degree centrality ( Huang et al, 2021 ), and decreased connectivity ( Zhang et al, 2020 ; Wan et al, 2021 ). When extended to a wider population of diabetes, the results are inconsistent.…”
Section: Discussionmentioning
confidence: 99%